2009
DOI: 10.1590/s1516-44462009000200015
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition in bipolar disorder: a critical review

Abstract: Affective and cognitive deficits in bipolar disorder vary according to the mood states. Follow-up studies re-testing bipolar disorder patients after recovery are needed in order to investigate if these abnormalities reflect a state or trait marker and can be considered an endophenotype. Future studies should aim at standardizing task and designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 44 publications
(65 reference statements)
5
50
1
13
Order By: Relevance
“…3,4 Significantly fewer studies have addressed empathy, a domain which can include cognitive and affective constructs. Cognitive empathy means cognitive understanding of the emotional state and point of view of the other person, hidden behind the emotion expressed.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Significantly fewer studies have addressed empathy, a domain which can include cognitive and affective constructs. Cognitive empathy means cognitive understanding of the emotional state and point of view of the other person, hidden behind the emotion expressed.…”
Section: Introductionmentioning
confidence: 99%
“…18 Second, there is notable overlap between the neurobehavioral functions modulated by OT and AVP in healthy adults with those that are abnormal in schizophrenia, such as social cognition and memory. [19][20][21][22] For example, AVP 1b knockout mice exhibit impairments in memory and social behavior. 23 Third, these hormones both regulate physiological activity in brain regions that have established functional and structural alterations in the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…37 Although OT and AVP have been implicated in schizophrenia, 14,38 the degree to which alterations in these hormone systems contribute to neurobehavioral deficits in schizophrenia and other psychotic disorders has not been systematically examined. Although supraphysiologic doses of OT modulate emotional and cognitive processes in healthy individuals 20,21 and in some small-sample schizophrenia studies, [39][40][41][42][43][44][45][46] it remains unclear whether there are altered physiological protein levels across these disorders and whether physiological levels of OT and AVP modulate neurobehavioral processes in schizophrenia and other psychotic disorders as in healthy individuals. Studies of endocrine levels and their neurobehavioral associations are needed to address these questions.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, several authors have reported social cognition deficits in patients with bipolar disorder (BD) both in euthymia [1][2][3] and during relapses. 4 A recent meta-analysis 5 showed that euthymic patients with BD exhibit a significant deficit in theory of mind (ToM), with a medium-large effect size (d = 0.79).…”
Section: Introductionmentioning
confidence: 99%